Mental health of British farmers. Issue 3 (1st March 2003) - Thomas, H V; Lewis, G; Thomas, D Rh; Salmon, R L; Chalmers, R M; Coleman, T J; Kench, S M; Morgan-Capner, P; Meadows, D; Sillis, M; Softley, P
Abstract : Aims: To estimate the prevalence of neurotic symptoms in a sample of British farmers, to investigate whether farming characteristics are associated with psychiatric morbidity, and to test the hypothesis that British farmers have a higher prevalence of depression and thoughts of life not worth living than the British household population. Methods: A total of 425 farmers from Hereford, Norwich, and Preston completed the Revised Clinical Interview Schedule (CIS-R) by computer between March and July 1999. The comparison cohort consisted of 9830 private householders aged 16–64 from the Office of Population Censuses and Surveys National Psychiatric Morbidity Surveys of Great Britain carried out in 1993 in which the CIS-R was administered. All analyses used the commands developed specifically for survey data available in Stata version 6.0. Results: Taking a threshold of an overall score of 12 or more on the CIS-R, only 6% of farmers reported clinically relevant psychiatric morbidity. Psychiatric morbidity was not significantly associated with farm type or size in this study. Farmers reported a lower prevalence of psychiatric morbidity than the general population but were more likely to report thinking that life is not worth living, particularly after the low prevalence of psychiatric morbidity had been taken into account (odds ratio 2.56, 95% CI 1.39 to 4.69). When restricting the comparison to only rural or semirural householders, this increased risk was even more pronounced (odds ratio 3.26, 95% CI 1.51 to 7.02). Conclusions: The relation between depression and suicidal ideation seems to be quite different among farmers and the general population and warrants further investigation. We have shown it is possible to measure mental health systematically in a sample of British farmers. This study should be repeated in the aftermath of the foot and mouth crisis.